Scanning SAXS–WAXS microscopy on osteoarthritis‐affected bone – an age‐related study. (4th February 2014) - Giannini, C.; Siliqi, D.; Ladisa, M.; Altamura, D.; Diaz, A.; Beraudi, A.; Sibillano, T.; De Caro, L.; Stea, S.; Baruffaldi, F.; Bunk, O.
<x xml:space="preserve">Abstract</x> Osteoarthritis (OA), among other bone pathologies, is expected to determine supramolecular changes at the level of the mineralized collagen fiber. In a proof‐of‐principle study, bone biopsies were collected from six coxarthritis‐affected patients, aged 62–87 years, during hip prosthesis implant surgery, sliced down to 100 µm‐thick tissues, and investigated using scanning small‐angle and wide‐angle X‐ray scattering (SAXS and WAXS) transmission microscopy. A multi‐modal imaging evaluation of the SAXS and WAXS data, combined with principal component and canonical correlation analyses, allowed the transformation of the raw data into microscopy images and inspection of the nanoscale structure of the mineralized collagen fibers across mm2 tissue areas. The combined scanning SAXS and WAXS microscopy is shown to be a suitable choice for characterizing and quantifying the nanostructural properties of collagen over extended areas. The results suggest the existence of a correlation between age and cross‐linking‐induced rigidity of collagen fibers.